The Phenomenon of Private Chatting in the View of the Hadith on the Prohibition of Seclusion - Maharani, Nyayu Nurlaili; Hasanah, Uswatun; M Nur, Sulaiman (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2024)
This article analyzes the phenomenon of private chatting in the context of the application of the hadith that prohibits seclusion between men and women who are not mahram. In today's digital era, interactions through messaging applications and social media are becoming increasingly widespread, often carrying implications for the social boundaries regulated in Islam. Although this phenomenon is often trivialized, the impact of private chatting can be quite harmful and lead to undesirable consequences. This research aims to discuss the phenomenon of private chatting from the perspective of hadith. Using a qualitative approach, this study explores the understanding of Muslim communities regarding the prohibition of seclusion and how they interpret and apply this principle in online communication. The author identifies various motivations that drive individuals to engage in private chatting, including the desire to build closer relationships, share information, and create a more intimate communication space. However, the study also highlights potential risks and negatives that may arise from such practices, such as the abuse of trust and the occurrence of immoral actions. The study concludes the relevance of the private chatting phenomenon to the hadith on the prohibition of seclusion, which can be linked due to the shared context of men and women being together without being mahram, and the illat generated through chatting that can fall under what is prohibited in Islam. Thus, this article argues the need for a deeper understanding of the hadiths about the prohibition of seclusion, as well as the enforcement of ethical values in online communication, to align with the principles of Islamic law.